Relationship between background factors and female marital satisfaction. - Mirfardi, Asghar; Edalati, Ali; Redzuan, Ma'arof (Science Publications, 2010)
In spite of the importance of marital satisfaction in couple relation, there is a little research in the Iranian context that examined the relationship between background factors and marital satisfaction. Thus, this study examined the relationship between duration of marriage, number of children, years of education and family income with female marital satisfaction. Approach: The study was carried out among a sample of 337 wives in Shiraz City, Iran. The Kansas Marital Satisfaction (KMS) was used to measure marital satisfaction. The study employed correlations test to determine the relationships between duration of marriage, number of children, years of education and family income with marital satisfaction. Results: The study found that there were no significant relationships between duration of marriage and family income and marital satisfaction. There was a negative significant relationship between respondents’ age and number of children and marital satisfaction. There was a positive significant relationship between respondents’ years of education and marital satisfaction. The Multivariate Regression Analysis was used to answer the last objective. The analysis showed that the predictor variable, women age, was found to be significant in explaining the observed variation in marital satisfaction (DV). Conclusion: Generally, the final model has explained 4% of total observed variance to marital satisfaction.